PENYULUHAN MANAJEMEN PEMBIAYAAN LEMBAGA KEUANGAN SYARIAH DI DESA CIAMPEA BOGOR - Mursyidah, Azizah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
This community service project aimed to introduce and socialize the management of Sharia financial institution financing in Ciampea Village, Bogor, emphasizing adherence to Islamic principles, particularly the prohibition of riba (interest). The project utilized a methodology of counseling, socialization, and basic training on various Sharia financing models. Key stages involved preparation, implementation of training (covering principles, history, and contracts like mudharabah, musyarakah, and murabahah), and evaluating participant comprehension. Ciampea Village demonstrates significant economic potential, driven primarily by the agricultural and MSME (Micro, Small, and Medium Enterprises) sectors. The core principles of Sharia financing—justice, cooperation, and mutual support—ensure equitable benefits. The 5C framework was used for borrower evaluation. The conclusion highlights a promising growth potential for Sharia financing in Ciampea, offering a comprehensive solution for economic needs. Implementing these fair financial practices is expected to sustainably enhance community welfare.